The republic of kazakhstan and revival of «New silk road» (Journal of Oriental Studies, 2017)
«New Silk Road project is mutually beneficial and relevant to globalization trends for both Central Asia and Europe. New Silk Road has a number of strategic advantages that can contribute to unity of the countries of Eurasian Continent and to achieving their economic potential».